-2x+3(3x-6)=-2-9x

Simple and best practice solution for -2x+3(3x-6)=-2-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+3(3x-6)=-2-9x equation:


Simplifying
-2x + 3(3x + -6) = -2 + -9x

Reorder the terms:
-2x + 3(-6 + 3x) = -2 + -9x
-2x + (-6 * 3 + 3x * 3) = -2 + -9x
-2x + (-18 + 9x) = -2 + -9x

Reorder the terms:
-18 + -2x + 9x = -2 + -9x

Combine like terms: -2x + 9x = 7x
-18 + 7x = -2 + -9x

Solving
-18 + 7x = -2 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-18 + 7x + 9x = -2 + -9x + 9x

Combine like terms: 7x + 9x = 16x
-18 + 16x = -2 + -9x + 9x

Combine like terms: -9x + 9x = 0
-18 + 16x = -2 + 0
-18 + 16x = -2

Add '18' to each side of the equation.
-18 + 18 + 16x = -2 + 18

Combine like terms: -18 + 18 = 0
0 + 16x = -2 + 18
16x = -2 + 18

Combine like terms: -2 + 18 = 16
16x = 16

Divide each side by '16'.
x = 1

Simplifying
x = 1

See similar equations:

| 10(s-4)=-85 | | 2m-8=10+18 | | 3x+1y=392 | | 14x-9=11y | | 900000000000000000000000000000000+423523542546224624246426264462264264642426264426565374676585798966975685362431432134245436356457764575976980=x | | k-3(5)=12(5) | | 7-3x=x+3x | | X^2+11X+19=X-6 | | 7r+2=(5r-4) | | 8(3-5m)= | | 2(3x+3)+6(x-4)= | | 8x+17=-5(3-8x) | | 8.1-1.5x=-6.9 | | 3x^3+x^2-2=0 | | 2*5+x= | | -4(5y-6)-y=-3(y-4) | | 42y+4=16 | | 42y+4=17 | | 6.2m+3-1.9=-5.72 | | 8y=y+6+3 | | -(-(-k))-(-2)(-2+k)=-k-(4k+3) | | -2(6y-5)-y=-4(y-3) | | 15x+3=28+10x | | (5v+7)(5-v)=0 | | 8x+9=6x*15 | | -18-x=12 | | 0.63m=-3 | | -4(6y-8)-y=-4(y-3) | | -[3x+(3x+9)]=9-(4x+3) | | X-2+x-3+123=180 | | 2y+12=21 | | 44=-4v |

Equations solver categories